Training bench design for practical valve coefficient determination, standard VDI/VDE 2173 - Roldán-Mckinley, Javier; Zambrano-Miranda, César Alejandro; Alonso-González, José Francisco; Campo-Escudero, Luis; Araújo-Segura, Ricardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
It is presented the design of a training bench for determining the flow coefficient of control valves, based on standard VDI/VDE 2173 that sets indications for this test. Preliminary sizing of the bench follows ergonomic considerations, taking into account the Colombian population anthropometrics. Structural elements of the device are designed by contrasting both failure analysis equations with finite element analysis results using SolidWorks.